ANALISIS KINERJA KEUANGAN PADA RESTAURAN MONTERO - Lestari, Wahyunita (EKONOMIA, 2013)
WAHYUNITA LESTARI,2012, Faculty of Economic, University August 17, 1945 Samarinda in East Borneo, Financial Performance Analysis at Restaurant Montero Sangatta (under the guidance of Titin and Herianto). The purpose and the writing is for information and consideration for leadership Restaurant Montero in Sangatta that can be used for the continued operation of restaurant. Reference materials for further research to certain parties who wantto know about the financial performance based on the ratio of Profitability, Liquidity, and Solvency. In accordance with the purpose of writing this, the principal issues raised : â€œIs Montero Restaurant financial performance improved in 2011compared to 2010 and 2009â€.Based on the issues identified earlier, the authors propose the following hypotheses : â€œIt is believed that the growth of liquidity, solvency and profitability Restaurant Montero in 2011, an increase from the year 2008, 2009, 2010. To analyze the data and test the validity of hypotheses have been put forward previously, the authors use the method of analysis is the analysis of the liquidity ratio, profitability, and solvency.